Association of the polymorphisms of chemokine genes (IL8, RANTES, MIG, IP10, MCP1 and IL16) with the pathogenesis of autoimmune thyroid diseases. (3rd July 2016) - Akahane, Maiko; Watanabe, Mikio; Inoue, Naoya; Miyahara, Yumi; Arakawa, Yuya; Inoue, Yuka; Katsumata, Yuka; Hidaka, Yoh; Iwatani, Yoshinori
Abstract: Chemokines induce leukocyte chemotaxis and contribute to chronic inflammation. To clarify the association between functional polymorphisms in genes encoding some chemokines and the pathogenesis of Autoimmune thyroid disease (AITD), we genotyped IL8 −251T/A, Regulated upon Activation, Normal T cell Expressed and presumably Secreted ( RANTES ) − 403G/A, −28C/G, MIG rs2276886G/A, IP10 −1596C/T, Monocyte Chemoattractant Protein1 ( MCP1 ) − 2518G/A and IL16 −295T/C polymorphisms. We genotyped these polymorphisms using the PCR-RFLP method in 149 Graves' disease (GD) patients, including 59 patients with intractable GD and 53 patients with GD in remission, as well as 131 Hashimoto's disease (HD) patients, including 54 patients with severe HD, 46 patients with mild HD and 99 healthy controls. The IL8 −251TT genotype and MIG rs2276886 A allele were more frequent in patients with AITD ( p  = 0.0139 and p  = 0.0005, respectively). The RANTES  − 403AA and −28GG genotypes were less frequent in patients with AITD ( p  = 0.0164 and p  = 0.0221, respectively). The MCP1 −2518GG genotype was more frequent in HD patients ( p  = 0.0323). The MIG rs2276886 AG genotype was less frequent in patients with intractable GD ( p  = 0.0051). Interestingly, the age of onset in GD patients with the RANTES  − 28CC genotype was younger than in those with −28CG and GG genotypes ( p  = 0.0028). In this study, we first reported that the polymorphisms in IL8, RANTES and MIG genes are associated with the development of AITD, and that the MIG rs2276886 AG genotype is associated with the intractability of GD. The RANTES  − 28CC genotype is associated with young onset of GD.